Christian Friedrich Freyer's 'Neuere Beiträge zur Schmetterlingskunde mit Abbildungen nach der Natur': an analysis with new data on its publication dates (Insecta, Lepidoptera) - Olivier, Alain (Contributions to Entomology = Beiträge zur Entomologie, 2000)
Christian Friedrich Freyer's (1794-1885) 'Neuere Beiträge zur Schmetterlingskunde mit Abbildungen nach der Natur' ([1831]-1858) is analysed, with a special focus on the publication dates of the 120 parts, that make up the seven volumes of this classical work in lepidopterology. First, a biographical sketch of the famous author is presented, based on information derived from the only known obituary by Wulzinger (1887), completed with data from Freyer's work. Then the 'Neuere Beiträge' itself is reviewed, highlighting its basic concept as well as the various origins of the material dealt with, the many contacts of Freyer and, ultimately, the impact of this achievement on his contemporaries. The numerous parts of the 'Neue Beiträge' are dated based on previous results by Tremewan (1988), wich were largely obtained from the printed wrappers of a copy of the work kept at the British Museum (Natural History) [now The Natural History Museum, London], as well as on an analysis of the contemporary literature. The results are given in accordance with ICZN 1999, Art. 21. Finally, a chronologically arranged checklist of nominal species-group taxa described, figured, or mentioned by Freyer in his 'Neuere Beiträge' is presented, with 245 available names applying to newly described species-group taxa marked either by one asterisk (for all lepidopterans except butterflies: 193 entries) or two asterisks (butterflies only: 52 entries).KeywordsLepidoptera, Christian Friedrich Freyer, literature, nomenclature, publication dates.